Empirical Validation of “G-D’s Physics’” “UNCIARE Critical Prediction” Discards “Dark-Matter” as “Superfluous”! - Bentovish, Jehonathan (European Journal of Applied Sciences, 2023)
Despite numerous experimental efforts to “detect” the presence of “Dark-Matter” (DM) over the past two decade (assumed to comprise up to 95% of all the mass in the universe), no direct experimental evidence of DM has been found to date. But, without the existence of “dark-matter” the accelerated rate of the universe’s expansion cannot be explained? Fortunately, a new alternative “G-D’s Physics” (previously termed: the “Computational Unified Field Theory”) was discovered that offers an alternative explanation for the accelerated expansion of the universe – while discarding “dark-matter” as “superfluous” (i.e., non-existent”). Based on direct empirical validation of two unique “Critical Predictions” of the “G-D’s Physics”, as more valid than the corresponding predictions of both General Relativity Theory (GRT) and Quantum Mechanics (QM) the” G-D’s Physics” is accepted as the new satisfactory Physics Paradigm for 21st century Theoretical Physics; Specifically, empirical validation of the “G-D’s Physics” “Universe’s Non-Continuous Increase in its Accelerated Rate of Expansion (UNCIARE) “Critical Prediction” as evidenced by the “Astronomical-Cosmological Gap in the Universe’s Accelerated Rate of Expansion” (ACGUARE) negates the possibility of the existence of “dark-matter”. The (purely hypothetical) existence of DM is further negated based on the G-D’s Physics “Computational Duality Principle” Theoretical Postulate, which points at the G-D’s Physics singular higher-ordered “Universal Computational Principle” (UCP) that simultaneously computes every exhaustive spatial pixel in the universe at the incredible rate of “c2/h” = 1.36-50 (sec’)! The new G-D’s Physics Paradigm is also shown to resolve the apparent “theoretical inconsistency” between GRT & QM and completely unify between the four basic physical features of “space”,” time”, “energy” & “mass”, based on a newly discovered “Universal Computational Formula” (UCP).